On the importance of Chinese investment in Africa - Ficawoyi Donou-Adonsou; Sokchea Lim (Review of Development Finance, 2018)
With the growing presence of China in Africa over the last two decades, this paper investigates the impact of Chinese foreign direct investment (FDI) on economic performance in Africa, which we compare to that of the traditional economic partners of African countries, including the U.S., France, and Germany. Also, we explore whether China's new relationship with Africa has somehow altered the preexisting relationship between Africa and its traditional partners. Our results, using the fixed-effects and instrumental variable approaches to 36 countries over the period 2003-2012, indicate that Chinese FDI improves income in Africa. We also find that the impact is more pronounced for U.S. and German investment. Moreover, there is evidence that Chinese investment crowds out U.S. investment in Africa, whereas France seems to be competing with China. These results imply that as the Chinese economy grows, the demand for resources has increased its intensive competition with the U.S. rather than with France.
Keywords: F21; O11; O55; 650; Foreign direct investment; Standard of living; Africa